The European unemployment problem in a globalized world: Wage rigidities, welfare and involuntary low-skilled labour unemployment - Bodo Hilgers; Ulrich Wacker (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 1999)
In a general equilibrium model of a small open economy with a nontraded goods sector involuntary low-skilled labour unemployment is introduced by an exogenously given wage rate, orientating ourselves by what has been called in the literature the 'European scenario'. By the concept of constrained and unconstrained transfer and profit functions we analyse the impact of a change both in an exogenously given low-skilled labour wage rate and in terms-oftrade on employment and welfare. As a striking result we will show that an increase in the exogenously given wage does not necessarily imply the expected decrease in employment and welfare. Thus, it will become obvious that not the distortion as such is decisive but its general equilibrium effects. We will derive necessary and sufficient conditions for an increase in employment and welfare due to an increase in the exogenously given wage. For improvements in employment and welfare the direction of change in the nontraded goods price and, thus, the output effect shows to be the driving force in our model. A terms of trade improvement leads to an employment effect that can either be positive or negative. In consequence, a decrease in employment can go hand in hand with an increase in welfare. In the case of a terms-of-trade deterioration, welfare only increases if employment increases.
Keywords: 330